1997
DOI: 10.1073/pnas.94.12.6553
|View full text |Cite
|
Sign up to set email alerts
|

Cloning gibberellin dioxygenase genes from pumpkin endosperm by heterologous expression of enzyme activities in Escherichia coli

Abstract: Gibberellin (GA) plant hormones are biosynthesized via complex pathways, the final steps of which are catalyzed by 2-oxoglutarate-dependent dioxygenases. Here, the cloning of two such enzymes, the GA 7-oxidase and the GA 20-oxidase, is reported using a novel approach, namely, by screening for GA dioxygenase activities expressed as T7 gene 10 fusion proteins in recombinant Escherichia coli. In vitro translation products of mRNA from endosperm of immature pumpkin seeds contained three GA dioxygenase activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…The PCR product was cloned in the pGEM-T Easy vector (Promega), and its sequence was determined to confirm the apparent GA 20-oxidase identity. Sequence comparison against genes in the database by the BLAST search program showed that its deduced amino acid sequence is highly homologous to the GA 20-oxidase from various plant species (Lange et al, 1994;Phillips et al, 1995;Xu et al, 1995;Garcia-Martinetz et al, 1997;Lange, 1997;MacMillan et al, 1997).…”
Section: Isolation Of a Cdna Homologous To Ga 20-oxidasementioning
confidence: 99%
See 3 more Smart Citations
“…The PCR product was cloned in the pGEM-T Easy vector (Promega), and its sequence was determined to confirm the apparent GA 20-oxidase identity. Sequence comparison against genes in the database by the BLAST search program showed that its deduced amino acid sequence is highly homologous to the GA 20-oxidase from various plant species (Lange et al, 1994;Phillips et al, 1995;Xu et al, 1995;Garcia-Martinetz et al, 1997;Lange, 1997;MacMillan et al, 1997).…”
Section: Isolation Of a Cdna Homologous To Ga 20-oxidasementioning
confidence: 99%
“…1). The watermelon protein shares 76% and 63% identities with the GA 20-oxidases of M. macrocarpus (MacMillan et al, 1997) and pumpkin (Lange, 1997), respectively. The protein also shares Ͼ50% identity with the GA 20-oxidases of pea (Garcia-Martinez et al, 1997), bean (Garcia-Martinez et al, 1997), Arabidopsis (Phillips et al, 1995), spinach (Wu et al, 1996), and lettuce (Toyomasu et al, 1998).…”
Section: Isolation Of a Cdna Homologous To Ga 20-oxidasementioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17][18][19][20][21][22][23] Some evidence has been accumulating that suggests GA plays in the formation and development of zygotic embryos. For instance, relatively high levels of GAs were observed in an early stage of zygotic embryos in stenospermocarpic grape 24) and maize.…”
mentioning
confidence: 99%